Gli Ultimi Avvisi di Maria (Loreto, 1797) - Fontana Castelli, Eva (Studi e materiali di storia delle religioni, 2019)
The Marian miracles spread in the papal state and in Rome between 1796 and 1797, the wide spread of prophecies with apocalyptic and millennial content born from religious and spiritual tension in the period preceding the proclamation of the Jacobean Roman Republic find a perspective of deepening in the analysis of some unpublished documents kept at the Archivum Romanum Societatis Iesu. These documents refer to and show the visions and "inspirations" received by Niccolò Paccanari, founder of an institute of Ignatian inspiration during the period of suppression of the Jesuit order. The spiritual formation, the religious imagery of this young cleric, a former soldier of the papal army, and the tones with which he translated his supernatural experience were strongly influenced, as well as by the prophecies of the resurgence of the Ignatian order also by the Franciscan spirituality. During the retreat at the Marian shrine of Loreto, Paccanari wrote The Last Warnings of Mary, a collection of revelations communicated by the Virgin, but also a sort of new Spiritual Exercises for "the last days of Humanity".